Antitumor activity and safety of camrelizumab plus famitinib in patients with platinum-resistant recurrent ovarian cancer: results from an open-label, multicenter phase 2 basket study. Issue 1 (11th January 2022) - Xia, Lingfang; Peng, Jin; Lou, Ge; Pan, Mei; Zhou, Qi; Hu, Wenjing; Shi, Huirong; Wang, Li; Gao, Yunong; Zhu, Jianqing; Zhang, Yu; Sun, Rong; et al.
Abstract : Background: Combination treatments with immune-checkpoint inhibitor and antiangiogenic therapy have the potential for synergistic activity through modulation of the microenvironment and represent a notable therapeutic strategy in recurrent ovarian cancer (ROC). We report the results of camrelizumab (an anti-programmed cell death protein-1 antibody) in combination with famitinib (a receptor tyrosine kinase inhibitor) for the treatment of platinum-resistant ROC from an open-label, multicenter, phase 2 basket trial. Methods: Eligible patients with platinum-resistant ROC were enrolled to receive camrelizumab (200 mg every 3 weeks by intravenous infusion) and oral famitinib (20 mg once daily). All patients had disease progression during or <6 months after their most recent platinum-based chemotherapy. Primary endpoint was confirmed objective response rate (ORR) per Response Evaluation Criteria in Solid Tumors (RECIST) V.1.1 based on investigator's assessment. Secondary endpoints included disease control rate (DCR), duration of response (DoR), time to response (TTR), progression-free survival (PFS), overall survival (OS), 12-month OS rate and safety profile. Results: Of the 37 women enrolled, 11 (29.7%) patients had primary platinum resistant, 15 (40.5%) patients had secondary platinum resistant and 11 (29.7%) patients had primary platinum refractory disease. As the cut-off date of April 9, 2021, nine (24.3%) patients had achieved a confirmed objective response, the ORR was 24.3% (95% CI, 11.8 to 41.2) and the DCR was 54.1% (95% CI, 36.9 to 70.5). Patients with this combination regimen showed a median TTR of 2.1 months (range, 1.8–4.1) and a median DoR of 4.1 months (95% CI, 1.9 to 6.3). Median PFS was 4.1 months (95% CI, 2.1 to 5.7), and median OS was 18.9 months (95% CI, 10.8 to not reached), with the median follow-up duration of 22.0 months (range, 12.0–23.7). The estimated 12-month OS rate was 67.2% (95% CI, 49.4 to 79.9). The most common ≥grade 3 treatment-related adverse events were hypertension (32.4%), decreased neutrophil count (29.7%) and decreased platelet count (13.5%). One (2.7%) patient died of grade 5 hemorrhage that was judged possibly related to study treatment by investigator. Conclusion: The camrelizumab with famitinib combination appeared to show antitumor activity in heavily pretreated patients with platinum-resistant ROC with an acceptable safety profile. This combination might provide a novel alternative treatment strategy in platinum-resistant ROC setting and warranted further exploration. Trial registration number: NCT03827837 .